2002
DOI: 10.1104/pp.006007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Jasmonate Biosynthesis in Arbuscular Mycorrhizal Barley Roots,

Abstract: Colonization of barley (Hordeum vulgare cv Salome) roots by an arbuscular mycorrhizal fungus, Glomus intraradices Schenck & Smith, leads to elevated levels of endogenous jasmonic acid (JA) and its amino acid conjugate JA-isoleucine, whereas the level of the JA precursor, oxophytodienoic acid, remains constant. The rise in jasmonates is accompanied by the expression of genes coding for an enzyme of JA biosynthesis (allene oxide synthase) and of a jasmonate-induced protein (JIP23). In situ hybridization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
2
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(142 citation statements)
references
References 37 publications
8
122
2
10
Order By: Relevance
“…The AM seedlings had 28.2 and 40.4% significantly higher root MeJA level than the non-AM seedlings under the WW and the DS conditions, respectively. The increase of MeJA by mycorrhization, in this study, is in agreement with the previous results as shown for several plant species (Hause et al, 2002;Meixner et al, 2005). As stated by LudwigMüller (2010), JA contributed to the life cycle of the AM fungus.…”
Section: Mejasupporting
confidence: 82%
“…The AM seedlings had 28.2 and 40.4% significantly higher root MeJA level than the non-AM seedlings under the WW and the DS conditions, respectively. The increase of MeJA by mycorrhization, in this study, is in agreement with the previous results as shown for several plant species (Hause et al, 2002;Meixner et al, 2005). As stated by LudwigMüller (2010), JA contributed to the life cycle of the AM fungus.…”
Section: Mejasupporting
confidence: 82%
“…Jasmonic acid concentrations were nine times higher in mycorrhizal plants than in non-mycorrhizal shoots, similar level of increase have been reported in mycorrhizal barley [22] and Medicago trucatula [47] . JA may be a systemic signal and dislocated throughout the plant [34] .…”
Section: Discussionsupporting
confidence: 51%
“…Likewise, an increase of IAA in AM onion (Torelli et al, 2000), AM litchi (Yao et al, 2005) and AM soybean (Meixner et al, 2005) was also well documented. In AM barley and cucumber, considerably higher JA levels had been observed, compared to non-AM controls (Hause et al, 2002;Vierheilig and Piche, 2002). The present study indicated the significantly higher root ZR, MeJA, and ABA concentrations in AMF seedlings than non-AMF seedlings.…”
Section: Discussionsupporting
confidence: 55%